Impact on testicular function of a single ablative activity of 3.7 GBq radioactive iodine for differentiated thyroid carcinoma. Issue 8 (15th June 2018) - Bourcigaux, N; Rubino, C; Berthaud, I; Toubert, M E; Donadille, B; Leenhardt, L; Petrot-Keller, I; Brailly-Tabard, S; Fromigué, J; de Vathaire, F; Simon, T; Siffroi, J P; et al.
Abstract: STUDY QUESTION: What are the consequences of radioactive iodine (RAI) therapy for testicular function? SUMMARY ANSWER: A single activity of 3.7 GBq RAI for differentiated thyroid carcinoma (DTC) treatment in young men transiently altered Sertoli cell function and induced sperm chromosomal abnormalities. WHAT IS KNOWN ALREADY: Few studies, mainly retrospective, have reported the potential impacts of RAI on endocrine and exocrine testicular function. STUDY DESIGN, SIZE, DURATION: A longitudinal prospective multi-center study on testicular function performed in DTC patients before a single 131 I ablative activity of 3.7 GBq (V0) and at 3 months (V3) and 13 months (V13) after treatment. PARTICIPANTS/MATERIALS, SETTING, METHODS: Forty male patients, aged 18–55 years, with DTC participated. Hormonal analysis included FSH, LH, testosterone and inhibin B serum levels at V0, V3 and V13. Furthermore, sperm parameters, DNA fragmentation and sperm chromosomal abnormalities were evaluated at each time points. The differences in all parameters, between V0–V3, V0–V13 and V3–V13, were analyzed, using a Wilcoxon test. MAIN RESULTS AND THE ROLE OF CHANCE: Prior to RAI administration, all patients had normal gonadal function. At V3, a statistically significant increase in FSH levels and a decrease in inhibin B levels were observed and sperm concentration, as well as the percentage of morphologically normal spermatozoa, were significantly decreased ( P < 0.0001). These modifications were transient as both sperm concentration and normal morphology rate returned to baseline values at V13. However, at this later time point, FSH and inhibin B levels were still impacted by RAI administration but remained in the normal range. Although no DNA fragmentation was observed at V3 nor V13, our study revealed a statistically significant increase in the number of sperm chromosomal abnormalities both at V3 ( P < 0.001) and V13 ( P = 0.01). LIMITATIONS, REASONS FOR CAUTION: Among the 40 patients included in the study, only 24 had all the parameters available at all visits. WIDER IMPLICATIONS OF THE FINDINGS: Prospective studies with longer term follow up would be helpful to determine whether the chromosome abnormalities persist. These studies would be required before sperm banking should be suggested for all patients. However, sperm preservation for DTC patients who require cumulative radioiodine activities higher than 3.7 GBq should be proposed. STUDY FUNDING/COMPETING INTEREST(S): This study was supported by the Programme Hospitalier de Recherche Clinique, AP-HP (No. P040419). The authors report no conflict of interest in this work. TRIAL REGISTRATION NUMBER: NCT01150318.